Ultrasound guided musculoskeletal interventions: professional opportunities, challenges and the future of injection therapy. Issue 4 (December 2015) - Innes, Sue; Maybury, Mark; Hall, Alison; Lumsden, Gordon
Abstract: The demand for ultrasound guided injections for musculoskeletal presentations has increased in recent years as practitioners and patients seek verification of needle position. Musculoskeletal management pathways regularly include injection therapy for pain relief and are sometimes indicated as a single intervention but may need to be supported by rehabilitation. Workload in radiology departments has expanded in volume and complexity as radiologists perform new interventional procedures that require medical expertise. Innovative responses are required to meet the demand for ultrasound guided musculoskeletal injections; one option is offering appropriate education to musculoskeletal sonographers, enabling them to extend their current scope of practice. The role of the extended scope physiotherapist in the United Kingdom provides evidence that role diversification can produce excellent patient outcomes whilst preserving financial resources. The professional, legal and clinical requirements of extending service provision to include new clinical staff presents challenges that have to be met with strong leadership and the provision of high quality education in ultrasound guided interventions. There are many indicators that the patient experience is enhanced by guiding musculoskeletal injections, and access to this service has impact on patients' confidence in their treatment pathway.